Microglial reduction of colony stimulating factor‐1 receptor expression is sufficient to confer adult onset leukodystrophy. Issue 3 (20th October 2020) - Biundo, Fabrizio; Chitu, Violeta; Shlager, Gabriel G. L.; Park, Eun S.; Gulinello, Maria E.; Saha, Kusumika; Ketchum, Harmony C.; Fernandes, Christopher; Gökhan, Şölen; Mehler, Mark F.; Stanley, E. Richard
Abstract: Adult onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) is a dementia resulting from dominantly inherited CSF1R inactivating mutations. The Csf1r +/− mouse mimics ALSP symptoms and pathology. Csf1r is mainly expressed in microglia, but also in cortical layer V neurons that are gradually lost in Csf1r+/− mice with age. We therefore examined whether microglial or neuronal Csf1r loss caused neurodegeneration in Csf1r+/− mice. The behavioral deficits, pathologies and elevation of Csf2 expression contributing to disease, previously described in the Csf1r +/− ALSP mouse, were reproduced by microglial deletion ( MCsf1r het mice), but not by neural deletion. Furthermore, increased Csf2 expression by callosal astrocytes, oligodendrocytes, and microglia was observed in Csf1r +/− mice and, in MCsf1r het mice, the densities of these three cell types were increased in supraventricular patches displaying activated microglia, an early site of disease pathology. These data confirm that ALSP is a primary microgliopathy and inform future therapeutic and experimental approaches. Main Points: Csf1r+/− dementia is reproduced by microglial, not neural, Csf1r heterozygosity. Microglial Csf1r heterozygosity causes expansion of Csf2 ‐expressing neuroglia and neuronal loss. Study supports microglial correction therapy & study of glia interactions.